Factors Influencing Green Logistics Adoption Intentions among Small and Medium Enterprises (SMEs) in Vietnam: An Empirical Study Based on the TOE Framework - Hai, Nguyen Thi Thanh (European Journal of Science, Innovation and Technology, 2026)
In an era of global environmental volatility, transitioning to sustainable practices has become a strategic imperative for Small and Medium Enterprises (SMEs) within the global value chain. This study investigates the factors influencing green logistics adoption intentions among SMEs in Vietnam by integrating the Technology-Organization-Environment (TOE) framework. Data were collected through a quantitative survey of 367 managers and owners of Vietnamese SMEs and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The empirical results indicate that all seven proposed hypotheses are supported. Notably, top management support and regulatory pressure emerged as the most significant predictors of adoption intention. Furthermore, while relative advantage and compatibility positively influence adoption, technological complexity remains a critical barrier. Market pressure and the quality of green human resources also play vital roles in driving the green transition. Theoretically, this research extends the applicability of the TOE framework to the SME context in an emerging market. Practically, the findings offer evidence-based insights for policymakers to design targeted support mechanisms and for SME managers to strategically align their operations with international environmental standards.